2013
DOI: 10.1186/1556-276x-8-544
|View full text |Cite
|
Sign up to set email alerts
|

Realization of radial p-n junction silicon nanowire solar cell based on low-temperature and shallow phosphorus doping

Abstract: A radial p-n junction solar cell based on vertically free-standing silicon nanowire (SiNW) array is realized using a novel low-temperature and shallow phosphorus doping technique. The SiNW arrays with excellent light trapping property were fabricated by metal-assisted chemical etching technique. The shallow phosphorus doping process was carried out in a hot wire chemical vapor disposition chamber with a low substrate temperature of 250°C and H2-diluted PH3 as the doping gas. Auger electron spectroscopy and Hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A conventional planar hetero-junction (P-HET) solar cell was prepared on polished wafer under the same procedure as RJ-HET solar cell. A RJ-HOMO solar cell was prepared on SiNWs by low temperature catalytic shallow diffusion technology 6 carried out in the Cat-CVD chamber under a substrate temperature of 250 C. H 2 -diluted PH 3 (0.5%) was used as the doping gas. Aer a 25 min doping, a junction depth of about 10 nm can be formed and a radial-homojunction structure can be obtained on the SiNWs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A conventional planar hetero-junction (P-HET) solar cell was prepared on polished wafer under the same procedure as RJ-HET solar cell. A RJ-HOMO solar cell was prepared on SiNWs by low temperature catalytic shallow diffusion technology 6 carried out in the Cat-CVD chamber under a substrate temperature of 250 C. H 2 -diluted PH 3 (0.5%) was used as the doping gas. Aer a 25 min doping, a junction depth of about 10 nm can be formed and a radial-homojunction structure can be obtained on the SiNWs.…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, Tian et al 3 rst reported a coaxial single SiNW based radial p-i-n solar cell prepared by vapor-liquid-solid technique which obtained a conversion efficiency of 3.4%. Aer that, with application of lithography and high temperature diffusion 4,5 or combination of metal-assisted chemical etching (MACE) and low temperature catalytic shallow doping, 6 radial p-n junction concept has been implemented on SiNWs arrays and reported efficiency increased up to >13%. However, the reported performances can still hardly meet people's expectation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the good candidates is heterojunction solar cells formed simply by depositing transparent semiconductor films on silicon substrates. The heterojunction solar cells have a number of potential advantages such as an excellent blue response, simple processing steps, and low processing temperatures …”
Section: Introductionmentioning
confidence: 99%
“…The formation of shallow p-n junctions in silicon (Si) is an important step in the fabrication of photovoltaic devices [1][2][3][4][5]. Using ion implantation, excimer laser annealing, and thermal diffusion of dopants into the Si wafer forming a p-n junction are expensive approaches [2,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%